Pengaruh metode dan waktu pinching terhadap pertumbuhan dan hasil tanaman marigold (Tagetes erecta L.) - Khoerun Nisa Zakiyatul Amaliyah; Muhammad Ridha Alfarabi Istiqlal; Inti Mulyo Arti (Universitas Djuanda, 2025)
Pinching is a cultivation technique intended to reduce apical dominance to stimulate lateral shoot growth and redirect plant energy toward flower formation. Apical dominance occurs when the apical bud grows more actively than lateral buds due to the influence of the auxin hormones. Previous studies mostly focused on the pinching methods at a single timing, so research on combinations of pinching methods and timing in marigold plants remains limited. This study aimed to analyze the effects of pinching methods and timing on the growth and yield of marigold (Tagetes erecta L.) plants. The research was conducted from January to May 2025 at UG Carte Field, Universitas Gunadarma Technopark (UGT), using a one-factor Randomized Complete Block Design (RCBD) with 10 treatments and 3 replications, resulting in 30 experimental units with 4 sample plants each. Treatments included: no pinching (P0), single pinching at 14 DAP (P1), single pinching at 21 DAP (P2), single pinching at 28 DAP (P3), 1⅟2 pinching at 14 DAP (P4), 1⅟2 pinching at 21 DAP (P5), 1⅟2 pinching at 28 DAP (P6), double pinching at 14 DAP (P7), double pinching at 21 DAP (P8), and double pinching at 28 DAP (P9). Observed variables included growth and yield parameters. The double pinching treatment at 28 DAT (P9) produced the highest number of secondary branches (47.33 branches) and number of leaves (328.83 leaves). Meanwhile, the single pinching treatment at 28 DAT (P3) resulted in the highest flower diameter (90.45 mm) and fresh weight per flower (30.07 g).